REPRESENTASI DIRI DALAM PEMILIHAN IDENTITAS VIRTUAL DI KALANGAN KOMUNITAS GAME ONLINE â€œCLOVERâ€ - Ramadona, Muhammad Rizki; Sari, Genny Gustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Technological developments bring people into a postmodern era where many online communities are formed and virtual communication has become a daily life in the community. In virtual communication identity is important because communicants are not face to face but rather communicate through intermediary text. Identity is closely related to the process of representation, because someone gets an identity when the existence is interpreted by others. Identity is an important part of self-concept. Self-concept is not just a descriptive picture, but also your judgment about yourself. Identity is a part of ourselves that we are known by others.The purpose of the research is to find out the self representation in the selection of virtual identities among members of the online game virtual community. This study uses qualitative methods, data collection techniques in this study are interviews and participant observation. The informant subjects were selected using purposive sampling technique, the informants in this study were 3 people from the Clover community members. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluations using the validity of data checking techniques, namely extension of equality and triangulation. The results of this study are the process of representation carried out by informants can produce a new identity that is used by informants in the virtual community online game Clover. Virtual identities that are formed from the process of self-representation of the Informants can be well received. Virtual identity that is in a different form from its real identity in the real world. New virtual identities that are shaped are influenced by several external factors, namely, social environment, reference groups, and idol figures. In this study we found a correlation between the time playing online games in a day with social interactions in the real world and cyberspace.Keyword: Self Representation, Indentity Virtual, Cyber Community